Identificação de possíveis ESTs de Eucalyptus relacionados a genes responsáveis pelo alongamento celular - Zimback, Léo; Mori, Edson Seizo [UNESP]; Moraes, Mário Luiz Teixeira de [UNESP]; Rosa, Daniel Dias [UNESP]; Furtado, Edson Luiz [UNESP]; Marino, Celso Luis [UNESP]; Maia, Ivan de Godoy [UNESP]; Wilcken, Carlos Frederico [UNESP]; Velini, Edivaldo Domingues [UNESP]; Guerrini, Iraê Amaral [UNESP]; Aoki, Hideyo (My University, 2012)
The objective of study was in silico mining of ESTs from Eucalyptus ESTs database (FORESTs, 2001) correlated with cell elongation genes of growth character. Using cDNA libraries, we identified similar EST clusters to the proteins involved on control of cell elongation have been registered on National Center of Biotechnologies Information – NCBI (2002). The data mining has shown similarities for the following ESTs clusters: EGEZLV2207D07.g with delta sterol reductase, EGEQRT4200A01.g with LKB brassinosteroid biosynthetic protein, EGJMLV2220C06.g with EMBL-transporter of mitochondrial half ABC, EGACST6260F07.g and EGMCFB1086B12.g with steroid 22-α hydroxylase, and EGEQSL1051D09.g with EGEZSL5201E08.g for copine protein.

O objetivo deste estudo foi buscar in silico os ESTs do Banco de dados do Genoma de Eucalyptus (FORESTs, 2001) correlacionados com genes de alongamento celular envolvidos com crescimento de forma geral. Utilizando bibliotecas de cDNA, nós identificamos agrupamentos de ESTs semelhantes às proteínas controlando alongamento celular registradas no National Center of Biotechnologies Information – NCBI (2002). A busca mostrou similaridade para os seguintes agrupamentos de ESTs: o agrupamento EGEZLV2207D07.g com a enzima esterol delta redutase, EGEQRT4200A01.g com a proteína LKB biossintética de brassinosteróide, EGJMLV2220C06.g com EMBL-transportador mitocondrial half ABC, EGACST6260F07.g e EGMCFB1086B12.g com esterol 22 alfa hidroxilase (CYP90) (P450) e EGEQSL1051D09.g com EGEZSL5201E08.g para a proteína copine.
Identification of possible ESTs of Eucalyptus related to genes responsible for cell elongation
Keywords: cDNA; mRNA; Protein similarity; Sequence alignments; cDNA; mRNA; Alinhamento de sequência; Similaridade protéica